PERSEPSI MAHASISWA FIP TERKAIT PENGGUNAAN WHATSAPP SEBAGAI MEDIA PEMBELAJARAN DARING - Khaerunnisa, Dita Sundari; Ramadhan, Anisya Rizki; Mauladan, Juanifar (EDUTECH, 2021)
Covid-19 virus forced the implementation of learning that was originally face to face become an online elarning the use of technology will be major aspects of it is inevitable in conducting onine learning. Many media outlets that learning can be used in online learning, one of the most attractive by teachers include. Whatsapp proven by the result of a conducted survey by the institutions of ensuring the quality of education (LPMP) Jawa Barat. This study attempts to find out how the perception of a faculty of education in Universitas Pendidikan Indonesia regarding the use of Whatsapp as a media for online learning. The data in this research obtained by the questioner that is distributed to respondents. The result of this research prove that the use of Whatsapp have a positive impact in online learning.Virus Covid-19 memaksa pelaksanaan pembelajaran yang semula tatap muka menjadi pembelajaran online penggunaan teknologi akan menjadi aspek utama yang tidak dapat dihindari dalam melakukan pembelajaran online. Banyak media pembelajaran yang dapat digunakan dalam pembelajaran online, salah satu yang paling diminati oleh guru antara lain. Whatsapp terbukti dari hasil survei yang dilakukan oleh Lembaga Penjamin Mutu Pendidikan (LPMP) Jawa Barat. Penelitian ini mencoba untuk mengetahui bagaimana persepsi fakultas pendidikan di Universitas Pendidikan Indonesia tentang penggunaan Whatsapp sebagai media pembelajaran online. Data dalam penelitian ini diperoleh dengan kuesioner yang dibagikan kepada responden. Hasil penelitian ini membuktikan bahwa penggunaan Whatsapp berpengaruh positif dalam pembelajaran online.